Dietary intake of pistachios or mixed nuts results in higher systemic antioxidant capacity with minimal effects on bone in adolescent male rats. (24th January 2023) - Wickman, Brooke E.; Clayton, Zachary S.; Rochester, Eric; Kern, Mark; Hong, Mee Young; Liu, Changqi; Hooshmand, Shirin
Abstract: Nutrition is a key determinant of bone health and attainment of peak bone mass. Excess oxidative stress induces bone loss while increasing antioxidant capacity promotes protective effects on bone. Nuts are rich in antioxidants; therefore, we tested the hypothesis that compared to a control diet high in fat (40 % energy) and cholesterol, diets containing isocaloric amounts of pistachios (8·1 % g/g) or mixed nuts (7·5 % g/g) for 8 weeks would result in greater bone health in male adolescent (3 weeks; a state of continued skeletal growth) Sprague-Dawley rats. We found no difference in bone mechanical properties among groups. Tibial apparent density was ~5 % higher in the pistachio and mixed nuts groups v . control ( P < 0·05) with no clear difference detected for the femur. Expressions of genes known to impact bone turnover and serum bone turnover biomarkers were unaffected by either diet relative to control. Serum antioxidant capacity was ~2-fold higher in the pistachio and mixed nuts groups compared with control ( P < 0·05) but were similar between groups. Therefore, pistachios and mixed nuts may increase tibial density, in part, due to increasing antioxidant capacity. Longer dietary interventions may be necessary to elicit detectable changes in other bones (e.g. femur) and to detect potential mechanisms for the possible bone protective effects of nuts.